1986
DOI: 10.1080/00288233.1986.10430452
|View full text |Cite
|
Sign up to set email alerts
|

Renovation of pastures containing paspalum 2. Effects of nitrogen fertiliser on the growth and persistence of overdrilled ryegrass

Abstract: The effects of nitrogen fertiliser on the growth and persistence of ryegrass seedlings transplanted into plots with high or low levels of paspalum were investigated in two field experiments over successive years. Ryegrass seedlings were introduced in July of each year, simulating autumn overdrilling, and were permanently identified. Rates of nitrogen varied from 48 to 67 kg/ha and were applied between August and October. Plots were grazed by cows at intervals. Half the plots were covered by wooden cages during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The pattern of high losses of newly sown endophyte-free ryegrass plants during the first summer/ autumn mimics that for high endophyte ryegrass (Thom et al 1986b;Thom et al 1993). However, pulling made a greater contribution to losses than was reported by Thom et al (1986a). Exceptionally dry and warm weather in summer/autumn 1998 continued the pattern of losses to levels of about 200-250 plants/m 2 , which were similar to stable plant numbers in other dairy pastures established by spray/drilling (Thom et al 1993).…”
Section: Plant Density and Sizesupporting
confidence: 65%
See 1 more Smart Citation
“…The pattern of high losses of newly sown endophyte-free ryegrass plants during the first summer/ autumn mimics that for high endophyte ryegrass (Thom et al 1986b;Thom et al 1993). However, pulling made a greater contribution to losses than was reported by Thom et al (1986a). Exceptionally dry and warm weather in summer/autumn 1998 continued the pattern of losses to levels of about 200-250 plants/m 2 , which were similar to stable plant numbers in other dairy pastures established by spray/drilling (Thom et al 1993).…”
Section: Plant Density and Sizesupporting
confidence: 65%
“…Tillering of seedlings is essential to their survival (Jewiss 1972), and a plant's ability to do this depends on availability of light and nutrients. Eliminating competition for these factors at the time of sowing aids establishment of ryegrass swards (Thom et al 1986a). Double spraying with glyphosate before sowing in autumn greatly reduced volunteer plant density, increasing the survival of sown plants (van Vught & Thom 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Standard procedures (Thom et al 1986) were used to determine the botanical composition of herbage collected from main plots in February, April and July 1995 (Period 1) and from subplots in September and December 1995, and March 1996 (Period 2). Ryegrass and Poa spp. tiller densities were estimated on 3 occasions from tiller counts in 2 randomly positioned frames (20 × 5 cm) per plot in Period 1, and in 2 frames per subplot in Period 2.…”
Section: Pasture Measurementsmentioning
confidence: 99%
“…During recent testing of further selections from the Mangere ecotype at four Waikato sites, a wide range of tolerances to "pulling" or the physical removal of clumps of ryegrass plants (plus 2-5 cm of roots) from the sward by cows during grazing was noted, suggesting a genetic component to the ryegrass pulling phenomenon. Losses of grass plants or tillers have often been associated with cattle grazing in summer-autumn (Hughes & Jackson 1974;Thom et al 1986) and some researchers have correlated increased pulling with increased use of nitrogen (N) fertiliser (Mitchell & Dickens 1979;Tallowin et al 1986). Many explanations of ryegrass pulling have appeared in the popular press (e.g., Anon 1992), but the relative importance of pulling to sward tiller density, herbage accumulation and persistence is not well defined for intensive dairying systems.…”
Section: Introductionmentioning
confidence: 99%
“…Summer drought, combined with high evaporation levels will severely limit ryegrass persistence (Waller & Sale 2001). Thom et al (1986a) also concluded that summer temperatures and dry periods in Waikato may lead to restrictions in ryegrass growth, survival and competitiveness, even in non-drought years. They found that high ryegrass losses occurred over summer (Thom et al 1986b).…”
Section: Discussionmentioning
confidence: 98%